Managing wilding pines in the Cape Floristic Region, South Africa: Progress and prospects - Grant Martin; Kim Canavan; Gerald Chikowore; Richard Bugan; Willem De Lange; Ben du Toit; Graham Harding; Ronald Heath; Martin Hill; Brett P. Hurley; Philip Ivey; Debbie Muir; et al. (South African Journal of Botany, 2025)

Biotransformation of aquaculture wastewater into aquatic feed protein source: Chlorella sorokiniana nutritional value and safety risk assessment - Cui Liu; Luohai Hua; Haokun Liu; Lan Wang; Xiaoming Zhu; Céline Rebours; Kevin Graham Harding; Lu Tan; Qiang Hu; Shouqi Xie (Journal of Environmental Management, 2024)

Refining the risk of HTLV-1-associated myelopathy in people living with HTLV-1: identification of a HAM-like phenotype in a proportion of asymptomatic carriers - Daniel Harding; Carolina Rosadas; Sandra Maria Tsoti; Amanda Heslegrave; Molly Stewart; Peter Kelleher; Henrik Zetterberg; Graham P. Taylor; Divya Dhasmana (Journal of NeuroVirology, 2022)
Up to 3.8% of human T-lymphotropic virus type-1 (HTLV-1)-infected asymptomatic carriers (AC) eventually develop HTLV-1-associated myelopathy (HAM). HAM occurs in patients with high (> 1%) HTLV proviral load (PVL). However, this cut-off includes more than 50% of ACs and therefore the risk needs to be refined. As HAM is additionally characterised by an inflammatory response to HTLV-1, markers of T cell activation (TCA), β 2 -microglobulin (β 2 M) and neuronal damage were accessed for the identification of ACs at high risk of HAM. Retrospective analysis of cross-sectional and longitudinal routine clinical data examining differences in TCA (CD4/CD25, CD4/HLA-DR, CD8/CD25 & CD8/HLA-DR), β 2 M and neurofilament light (NfL) in plasma in ACs with high or low PVL and patients with HAM. Comparison between 74 low PVL ACs, 84 high PVL ACs and 58 patients with HAM revealed a significant, stepwise, increase in TCA and β 2 M. Construction of receiver operating characteristic (ROC) curves for each of these blood tests generated a profile that correctly identifies 88% of patients with HAM along with 6% of ACs. The 10 ACs with this ‘HAM-like’ profile had increased levels of NfL in plasma and two developed myelopathy during follow-up, compared to none of the 148 without this viral-immune-phenotype. A viral-immuno-phenotype resembling that seen in patients with HAM identifies asymptomatic carriers who are at increased risk of developing HAM and have markers of subclinical neuronal damage.

Accumulation of Selenium and Lack of Severe Effects on Productivity of American Dippers (Cinclus mexicanus) and Spotted Sandpipers (Actitis macularia) - Lee E Harding; Mark Graham; Dale Paton (Archives of Environmental Contamination and Toxicology, 2005)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Hydrodynamic properties of mucins secreted by primary cultures of Guinea-pig tracheal epithelial cells: determination of diffusion coefficients by analytical ultracentrifugation and kinetic analysis of mucus gel hydration and dissolution - Sara Dodd; Graham A. Place; R. L. Hall; Stephen E. Harding (European Biophysics Journal, 1998)